“The grass is greener further away, right? Socio-geographic imaginaries and psycho-social motivations of short-term student mobilities - Ang, Ming Wei; Yang, Peidong; Toh, Yan Yun (Journal of International Students, 2026)
Singapore undergraduates prefer European destinations to Asian ones for semester-long exchanges, despite sustained efforts to enhance regional mobility within Asia. This research examines how ideological conditions, including socio-geographic imaginaries, sustain these preferences. We conducted semi-structured interviews with 63 local undergraduates from three universities in Singapore and used Causal Layered Analysis (CLA) to analyze emergent themes regarding worldviews, metaphors, and myths. We found that students’ preferences are discursively sustained by interlocking perceptions of cosmopolitan normativity, Asian homogeneity, and essentialized Asianness of Singapore’s identity. These worldviews are in turn stabilized by metaphors of distance (like “broadening horizons”) and the bildungsroman mythical journey of a fledgling leaving the nest, contextually salient to life stage experiences of Singaporean young adults. Our findings illustrate the importance of considering the interplay between socio-geographic imaginaries and the social meanings of specific mobility programs, extending limited research on the ideological factors shaping short-term student mobilities.